A review of the cost and effectiveness of solutions to address plastic pollution - Nikiema, Josiane; Asiedu, Zipporah (Springer, 2022)
Plastic usage increases year by year, and the growing trend is projected to continue. However as of 2017, only 9% of the 9 billion tons of plastic ever produced had been recycled leaving large amounts of plastics to contaminate the environment, resulting in important negative health and economic impacts. Curbing this trend is a major challenge that requires urgent and multifaceted action. Based on scientific and gray literature mainly published during the last 10 years, this review summarizes key solutions currently in use globally that have the potential to address at scale the plastic and microplastic contaminations from source to sea. They include technologies to control plastics in solid wastes (i.e. mechanical and chemical plastic recycling or incineration), in-stream (i.e. booms and clean-up boats, trash racks, and sea bins), and microplastics (i.e. stormwater, municipal wastewater and drinking water treatment), as well as general policy measures (i.e. measures to support the informal sector, bans, enforcement of levies, voluntary measures, extended producer responsibility, measures to enhance recycling and guidelines, standards and protocols to guide activities and interventions) to reduce use, reuse, and recycle plastics and microplastics in support of the technological options. The review discusses the effectiveness, capital expenditure, and operation and maintenance costs of the different technologies, the cost of implementation of policy measures, and the suitability of each solution under various conditions. This guidance is expected to help policymakers and practitioners address, in a sustainable and cost-efficient way, the plastic and microplastic management problem using technologies and policy instruments suitable in their local context.